The Effectiveness of Giving Plant PGPR Rhizosphere Bamboo on Cocoa Seeds Germination at The Nursery Level - Muhammad Yusril Hardiansyah; Yunus Musa; Abdul Mollah Jaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
The low productivity of cocoa plantations in Indonesia is partly due to the low quality of seeds, which refers to the impeded growth of cultivated cocoa nurseries. Seed is the initial growth of plants so the importance of giving special treatment to seeds will refer to better seed growth. Provision of Plant Growth Promoting Rhizobacteria (PGPR) microbes can produce indoleacetic acid (IAA) in plants to improve the quality of plant growth. This study aims to determine the effectiveness of the provision of Plant Growth Promoting Rhizobacteria bamboo rhizosphere against cocoa seed germination. The study was carried out in the farmer group garden, Gantarangkeke District, Bantaeng. This study was arranged in the form of a two-factor factorial design (F2F) in a randomized block design (RBD). The use of cocoa seed type as the first factor consisted of GTB (Gantarangkeke Bantaeng) local cocoa seed and MCC 01 cocoa seed and seed immersion treatment at PGPR rhizosphere bamboo concentration as the second factor consisting of 0% (control) concentration, 5%, 10 % and 15%. The results obtained indicate that administration of seeds with bamboo rhizosphere PGPR affects the germination (100.00%), the speed of seed growth (7.14%/etmal), as well as on abnormal seeds (10.00%). So that the provision of bamboo rhizosphere PGPR on cocoa seeds has an effective influence on seed germination and cocoa seedling development.